Community Service Lecture Caring for Education: Building a Quality Al-Quran Education Park in Puncak Alai Village - Wafiq Azizah; Amrina Amrina; Afbasri Afbasri; Thiago Rocha (Yayasan Adra Karima Hubbi, 2025)
Background. Al-Quran education parks are often faced with various challenges, such as lack of facilities, limited teaching staff, and suboptimal learning methods. Therefore, this real work lecture activity is here to provide a real contribution to improving the quality of education in the Al-Quran education park of Puncak Alai Village.Purpose. The Peduli Pendidikan real work lecture activity aims to improve the quality of religious education in the Al-Qur'an education park, Al-Qur'an education park, Nagari Puncak Alai. Method. This study uses a qualitative approach with an action research design. Data were collected through participant observation, in-depth interviews with teachers of the Al-Qur'an education park, administrators, and students, and documentation. Data analysis was conducted descriptively qualitatively with a focus on changes that occurred before and after the program was implemented.Results. The results of the study showed an increase in the quality of learning in the Al-Qur'an education park in Nagari Puncak Alai. This is indicated by the increasing enthusiasm of students in participating in teaching and learning activities, better understanding of religious materials, and improvements in the facilities and infrastructure of the Al-Qur'an education park. Conclusion. This Peduli Pendidikan real work lecture activity has succeeded in improving the quality of learning in the Al-Qur'an education park in Puncak Alai village.